2011
DOI: 10.5301/jn.5000056
|View full text |Cite
|
Sign up to set email alerts
|

Total parathyroidectomy improves survival of hemodialysis patients with secondary hyperparathyroidism

Abstract: Total parathyroidectomy was associated with better survival, probably due to decreased cardiovascular mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 0 publications
1
40
1
3
Order By: Relevance
“…Most studies adjusted a wide range of potential confounders to investigate the association between PTx and all-cause mortality, including age, sex, body mass index (BMI), diabetes, duration of dialysis, and dialysis modality. Twelve studies presented data with all-cause mortality [19][20][21][22][23][24][25][26][27][28][29]31 and six studies with cardiovascular mortality. 19,20,23,26,28,30 Table 1 lists the key characteristics of the 13 studies.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies adjusted a wide range of potential confounders to investigate the association between PTx and all-cause mortality, including age, sex, body mass index (BMI), diabetes, duration of dialysis, and dialysis modality. Twelve studies presented data with all-cause mortality [19][20][21][22][23][24][25][26][27][28][29]31 and six studies with cardiovascular mortality. 19,20,23,26,28,30 Table 1 lists the key characteristics of the 13 studies.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…Of them, 37 studies were retrieved for detailed evaluation, and finally 24 studies were excluded due to absence of information on the outcomes of interest (19 articles) or provision of data only in abstract form (5 articles). Finally, 13 studies [19][20][21][22][23][24][25][26][27][28][29][30][31] fulfilled the eligibility criteria ( Figure 1), with 10052 PTx-treated patients and 12001 medically-treated patients (totally 22053 patients). The 13 studies were all cohort studies with sample sizes from 20 to 4558 patients, and reported prevalence rates of diabetes from 0% to 44.3%.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…KBY'de paratiroidektomi operasyonu %10-30 hastaya uygulanıyor (27)(28)(29). Türk Nefroloji Derneği 2012 registry değerlerinde SHPT de ilaç kullanım oranlarına baktığımızda SHPT tanılı hastaların %46,36'sının tedavi aldığını tespit ettik.…”
Section: Bulgularunclassified
“…Evidence of potential survival benefit after parathyroidectomy came from retrospective studies (77,126,127) but one retrospective study suggested that patients with persistently very low PTH levels post-parathyroidectomy had a higher 5-year mortality (128). Furthermore, there is concern relating to bone turnover as parathyroidectomy is likely to turn high turnover bone disease to adynamic bone disease (129) which is also associated with worse vascular calcification (130).…”
Section: Surgicalmentioning
confidence: 99%